PENGARUH DIMENSI KEBIJAKAN PIMPINAN TERHADAP KINERJA ORGANISASI DINAS PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN BARITO TIMUR - Celiani Celiani; Muhammad Akbar; Anhar Yani (Administraus, 2018)
This study aims to: 1) To analyze the influence of leadership policy from the aspect of policy issues on the performance of the organization of the Regional Finance and Asset Management Office of East Barito Regency, 2) To analyze the influence of leadership policy from the alternative aspect of the policy on the performance of the organization of the District Financial Management and Asset Office East. 3) To analyze the influence of leadership policy from the aspect of policy action on the performance of the organization of the Regional Finance and Asset Management Office of East Barito Regency, 4) To analyze the influence of the leadership policy from the aspect of the policy result to the performance of the organization of the Regional Finance and Asset Management Office of East Barito Regency. This research is a quantitative descriptive research. The population in this study is all employees at the Office of Management of Finance and Assets Region of East Barito Regency as many as 59 (fifty nine) people. Sampling in this study was done by total sampling technique or total sample. Data were collected through questionnaires and documentation.The result of the research shows that: 1) Leadership policy from the aspect of policy problem gives positive but insignificant influence to the performance of the organization of the Regional Finance and Asset Management Office of East Barito Regency, 2) Leadership policy from the alternative aspect of policy gives positive and significant influence to organizational performance Regional Finance and Asset Management Office of Barito Regency. 3) Leadership policy from the aspect of policy actions gives a positive and significant impact on the performance of the organization of the Regional Finance and Asset Management Office of East Barito Regency. 4) Leadership policy from the aspect of policy result gives a positive and significant influence to the performance of the organization of the Regional Finance and Asset Management Office of East Barito Regency. Penelitian ini bertujuan : 1) Untuk menganalisis pengaruh kebijakan pimpinan dari aspek masalah kebijakan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur, 2) Untuk menganalisis pengaruh kebijakan pimpinan dari aspek alternatif kebijakan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur. 3) Untuk menganalisis pengaruh kebijakan pimpinan dari aspek tindakan kebijakan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur, 4) Untuk menganalisis pengaruh kebijakan pimpinan dari aspek hasil kebijakan terhadap kinerja organi.sasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur. Penelitian ini merupaka penelitian deskriptif kuantitatif. Populasi pada penelitian ini adalah seluruh pegawai pada Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur yaitu sebanyak 59 (lima puluh sembilan) orang. Pengambilan sampel dalam penelitian ini dilakukan dengan teknik total sampling atau sampel total. Data dikumpulkan melalui kuesioner dan dokumentasi. Hasil penelitian menunjukkan bahwa : 1) Kebijakan pimpinan dari aspek masalah kebijakan memberikan pengaruh yang positif namun tidak signifikan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur, 2) Kebijakan pimpinan dari aspek alternatif kebijakan memberikan pengaruh yang positif dan signifikan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito. 3) Kebijakan pimpinan dari aspek tindakan kebijakan memberikan pengaruh yang positif dan signifikan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur. 4) Kebijakan pimpinan dari aspek hasil kebijakan memberikan pengaruh yang positif dan signifikan terhadap kinerja organisasi Dinas Pengelolaan Keuangan dan Aset Daerah Kabupaten Barito Timur.